Tanwirul Fikr Student Boarding School Strategy in Forming Disciplined Behavior of Female Students-UNS Students - Zarya Eva Azzahra*; Dwi Astutik; Yosafat Hermawan Trinugraha (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to analyze the influence of background factors of UNS female students and identify strategies implemented by Tanwirul Fikr Student Boarding School in shaping their disciplinary behavior. The method used in this study is descriptive qualitative with a case study approach. The data used in this study were collected through observation and interview techniques, then analyzed using the Miles and Huberman interactive analysis model data analysis technique. The results of this study indicate that the disciplinary strategies implemented by Tanwirul Fikr Student Boarding School, which include education, regulations, special programs, guidance, and evaluation, are effective in shaping and improving the disciplinary behavior of UNS female students gradually, even though they have diverse backgrounds, such as attitude (personality), family, education, and social backgrounds. The variations in these strategies were then analyzed using the perspective of Emile Durkheim's social fact theory. Based on the theoretical analysis, Tanwirul Fikr Student Boarding School implements various strategies by regulating and implementing rules that must be obeyed and avoided during the study period. This includes values, norms, and regulations that are binding and influence individual UNS students.